Fermionic versus bosonic descriptions of one-dimensional spin-gapped antiferromagnets - Yamamoto, Shoji; Funase, Kei-ichi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
In terms of spinless fermions and spin waves, we describe magnetic properties of a spin-1/2 ferromagnetic–antiferromagnetic bond-alternating chain which behaves as a Haldane-gap antiferromagnet. On one hand, we employ the Jordan–Wigner transformation and treat the fermionic Hamiltonian within the Hartree–Fock approximation. On the other hand, we employ the Holstein– Primakoff transformation and modify the conventional spin-wave theory so as to restore the sublattice symmetry. We calculate the excitation gap, the specific heat, the magnetic susceptibility, magnetization curves, and the nuclear spin-lattice relaxation rate with varying bond alternation. These schemes are further applied to a bond-alternating tetramerized chain which behaves as a ferrimagnet. The fermionic language is particularly stressed as a useful tool to investigate one-dimensional spin-gapped antiferromagnets, while the bosonic one works better for ferrimagnets.